Analisis Perancangan Desain Produk Gadukan Guna Meningkatkan Daya Saing Industri Kecil Menengah - Ni Luh Putu Hariastuti; L. Lukmandono (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
Kampung Gadukan Surabaya, is a center of the village featured products ladies fashion bags in East Java. Foreign products, especially from China,became a threat to SME won in both domestic market and export market. Variations in product design and affordable price of make imported products more in demand by the public. Increased competitiveness through the realization of the strategy of product diversification as a strategy that needs to be done in the SME businesses expand reviews their markets. Through a gap analysis to obtain customer satisfaction criteria and refers to the eight dimensions of product development, the resulting that there are 20 criteria in product attributes are important by consumers. In addition, from the design concept of the initial design of products produced four factors of quality criteria that should be a priority in the product design process. The fourth factor is the quality of the quality of raw and auxiliary materials, elegant design, color and quality of the production process. Based on reviews these four factors, the quality of the products of SMEs will be expected to meet the desires of consumers.